Regional identity of young people in the Pomurje statistical region - Flegar, Špela; Konečnik Kotnik, Eva (Journal for Geography, 2020)
Spatial identity can exist on different levels - local, regional and global level. If we focus to the level of the region, we are talking about regional identity. In Slovenia, some surveys of regional identity have been made, joined by the present, carried out on a sample of young people living in the Pomurje statistical region. With the survey method we found that young people living in the Pomurje statistical region do not primarily identify themselves as Pomurians. Young people with permanent residence in the Pomurje region also show different levels of regional identity in different identity indicators. At the same time, they evaluate the region more positively and rate its potentials higher than the surveyed young people living outside the region.
Keywords: Young people; spatial identity; regional identity; Pomurje statistical region